PENYULUHAN HUKUM TENTANG LAHIRNYA KUHP BARU (UU NOMOR 01 TAHUN 2023) DARI PERSPEKTIF KEPASTIAN HUKUM & KEADILAN MASYARAKAT - Agung, Dirga; Tangko, Lidwina Apriliana Allo; Pratiwi, Andi Dewi (Gapenas Publisher, 2025)
The community service activities carried out by Dr. Dirga Agung, S.H., M.H., Lidwina Apriliana Allo Tangko, S.H., M.H., and Andi Dewi Pratiwi, S.H., M.H., which took place on January 5, 2026, held in the Community Meeting Room at the RT.002/RW.001 Neighborhood Watch Post, Mariso Village, Makassar City, has made a very meaningful contribution to the community, especially in Mariso Village, and was very well received with great enthusiasm. The legal counseling session on the enactment of the new Criminal Code (Law No. 01 of 2023) from the perspective of legal certainty and community justice was held as a way to understand and increase the legal awareness of the community of RT.002/RW.001, Mariso Village. so it is hoped that this legal counseling can be used as a first step to learn about and understand the changes in the new Criminal Code and the role of the community in increasing legal awareness in the Barombong Village neighborhood as a preventive measure to reduce the risk of misunderstandings and unresponsiveness among Barombong Village residents. Recently, there have been many reports regarding the understanding of the law that the old Criminal Code is still valid and has not been replaced, which is an issue that remains an important concern in the world of criminal law. On a broader scale, many people in big cities in Indonesia are not yet aware of the changes brought about by the new Criminal Code. In addition, the lack of public awareness of the dangers and risks of incorrect law enforcement among the community is the main cause of the recent increase in law enforcement problems throughout Indonesia